Identifying Critical Factors for Blockchain Technology Adoption in Indonesian E-Commerce - Harunur Rosyid; Umi Chotijah; Muhammad Zaky Al Mubarok; Didiary Shandy Setiyawan (JUSIFO : Jurnal Sistem Informasi, 2024)
This study examines the adoption of blockchain technology in Indonesian e-commerce by employing the Technology Acceptance Model (TAM) to identify key influencing factors. The research focuses on four blockchain characteristics: Time Saving, Cost Saving, Data Privacy Security, and Traceability. The findings indicate that Time Saving and Traceability significantly enhance Perceived Usefulness, while Cost Saving and Data Privacy Security do not have a notable effect. The study confirms that Perceived Usefulness significantly impacts Adoption Intention, mediated by Perceived Ease of Use. Despite the insights provided, the study acknowledges limitations, such as the focus solely on individual users and the use of only four blockchain characteristics. Future research should explore additional factors, such as efficiency and government support, and consider organizational users, like SMEs, to offer a comprehensive understanding of blockchain adoption. Overall, this study offers valuable insights into the critical determinants influencing blockchain adoption in Indonesian e-commerce, emphasizing the importance of perceived benefits in shaping user intentions.